Angiotensin Receptor-Neprilysin Inhibition in Chagas Cardiomyopathy: Clinical Practice Update - Skibicka, Katarzyna; Wesołowska, Weronika; Skibicki, Tomasz; Bujak, Robert (Journal of Education, Health and Sport, 2025)
Background: Chronic Chagas cardiomyopathy is an arrhythmogenic, fibrosis-prone form of heart failure that develops years after Trypanosoma cruzi infection. Standard therapy has largely been extrapolated from non-Chagas trials. Angiotensin receptor-neprilysin inhibition (ARNI) offers a biologically plausible approach by enhancing natriuretic peptide/cGMP signaling while attenuating the renin-angiotensin-aldosterone system. Objective: To summarize contemporary evidence on ARNI for heart failure due to Chagas disease, place eplerenone within guideline-directed therapy and translate these data into a practical treatment pathway. Results: Across broad HFrEF populations, ARNI reduces clinical events and NT-proBNP. In Chagas cardiomyopathy, prior evidence was limited; the Chagas-specific randomized trial presented at a scientific congress suggests a favorable hierarchical outcome with sacubitril/valsartan versus enalapril, driven primarily by early NT-proBNP reduction, with a safety profile consistent with prior experience. Eplerenone remains a complementary therapy targeting aldosterone-related fibrosis. A practical, stepwise pathway for implementation is outlined. Conclusions: For eligible patients with heart failure due to Chagas disease, transition to sacubitril/valsartan appears reasonable, with careful titration and routine laboratory surveillance; eplerenone represents a complementary option within complete guideline-directed therapy. Further peer-reviewed results from the Chagas-specific trial are needed to refine effect sizes and subgroup guidance.